Evaluation of a Humidified Nasal High-Flow Oxygen System, Using Oxygraphy, Capnography and Measurement of Upper Airway Pressures - Ritchie, J. E.; Williams, A. B.; Gerard, C.; Hockey, H. (Anaesthesia and intensive care, 2011)
In this study, we evaluated the performance of a humidified nasal high-flow system (Optiflow™, Fisher and Paykel Healthcare) by measuring delivered FiO 2 and airway pressures. Oxygraphy, capnography and measurement of airway pressures were performed through a hypopharyngeal catheter in healthy volunteers receiving Optiflow™ humidified nasal high flow therapy at rest and with exercise. The study was conducted in a non-clinical experimental setting. Ten healthy volunteers completed the study after giving informed written consent. Participants received a delivered oxygen fraction of 0.60 with gas flow rates of 10, 20, 30, 40 and 50 l/minute in random order. FiO 2 , F E O 2 , F E CO 2 and airway pressures were measured. Calculation of FiO 2 from F E O 2 and F E CO 2 was later performed. Calculated FiO 2 approached 0.60 as gas flow rates increased above 30 l/minute during nose breathing at rest. High peak inspiratory flow rates with exercise were associated with increased air entrainment. Hypopharyngeal pressure increased with increasing delivered gas flow rate. At 50 l/minute the system delivered a mean airway pressure of up to 7.1 cmH 2 O. We believe that the high gas flow rates delivered by this system enable an accurate inspired oxygen fraction to be delivered. The positive mean airway pressure created by the high flow increases the efficacy of this system and may serve as a bridge to formal positive pressure systems.